Aerospace Cluster of Bangalore: Can the SMEs Take up the Challenges? - Chandra N, Sharath; Shekar, G. L; Raghavendra, N. V (Journal of Asian Business Strategy, 2015)
As per estimates made by leading experts global civil aerospace industry is expected to touch revenue of US 45 billion. The industry is witnessing emergence of developing countries such as India, Brazil and China as players pivoted to play major role in future. Small and Medium Scale Enterprises (SME) in India have the potential to garner a major share in Tier-3 and Tier-4 sectors of aerospace value chain. Overseas aircraft manufacturers such as Airbus and Boeing have recognized the competencies and skills India has in areas such as engineering, production, maintenance & service, etc. In this backdrop, this paper explores the global scenario of SMEs in some of the successful clusters. Some of the prominent clusters discussed in this paper include the clusters at California & Seattle, Toulouse, Hamburg and Chengdu. This would help us in drawing useful lessons for the Bangalore cluster, which is highlighted in the paper. An analysis is done to identify major challenges that influence the future growth prospects of aerospace industry in Bangalore namely Infrastructure, Finance, Technology and Manpower. A summary and discussion of the opportunities and challenges faced by the Bangalore aerospace cluster and draws conclusions, which have a bearing on policy measures.